Interculturality through Native Skills and Indigenous Sports at the National University of Colombia - Rodríguez, Sebastián (2025)
Introduction: Indigenous communities have always fought for the recognition of their social, political and cultural rights. The 1991 Political Constitution of Colombia recognized cultural diversity and the responsibility to protect ethnic traditions and customs. Despite this, there is a gap between legislation and its effective application. That said, it is crucial to implement strategies to guarantee the adequate execution of regulations and actions to materialize such recognition. Objective: Faced with this challenging situation, the researchers of this experience have set the objective of recognizing ethnic and cultural diversity at the Universidad Nacional de Colombia, Bogota campus, through the promotion of indigenous skills and sports. Methodology: We planned and developed the first Community Sports and Skills Meeting, a historic event that took place on April 27, 2023 in the emblematic central square of the Universidad Nacional de Colombia. Results: In this meeting, the indigenous council of the Universidad Nacional led several activities. These included the presentation of traditional skills, games and indigenous sports of various ethnic communities. In addition, a discussion was organized on the role of community social sports in the social, cultural and sports development of ethnic communities. Cultural activities were also carried out, such as typical dances and music from different regions of the country. Conclusions: This meeting represents a significant step towards valuing cultural diversity in Colombia, marking a milestone in the history of the institution and society in general.